The Absence of PTEN in Breast Cancer Is a Driver of MLN4924 Resistance - Du, Meng-ge; Peng, Zhi-qiang; Gai, Wen-bin; Liu, Fan; Liu, Wei; Chen, Yu-jiao; Li, Hong-chang; Zhang, Xin; Liu, Cui Hua; Zhang, Ling-qiang; Jiang, Hong; Xie, Ping (Frontiers in Cell and Developmental Biology, 2021)
Background: Numerous studies have indicated that the neddylation pathway is closely associated with tumor development. MLN4924 (Pevonedistat), an inhibitor of the NEDD8-activating E1 enzyme, is considered a promising chemotherapeutic agent. Recently, we demonstrated that neddylation of the tumor suppressor PTEN occurs under high glucose conditions and promotes breast cancer development. It has been shown, however, that PTEN protein levels are reduced by 30-40% in breast cancer. Whether this PTEN deficiency affects the anti-tumor function of MLN4924 is unknown. Methods: In the present study, cell counting kit-8 and colony formation assays were used to detect cell proliferation, and a transwell system was used to quantify cell migration. A tumor growth assay was performed in BALB/c nude mice. The subcellular location of PTEN was detected by fluorescence microscopy. The CpG island of the UBA3 gene was predicted by the Database of CpG Islands and UCSC database. Western blotting and qRT-PCR were used to measure the expression of indicated proteins. The Human Protein Atlas database, the Cancer Genome Atlas and Gene Expression Omnibus datasets were used to validate the expression levels of UBA3 in breast cancer. Results: Our data show that the anti-tumor efficacy of MLN4924 in breast cancer cells was markedly reduced with the deletion of PTEN. PI3K/Akt signaling pathway activity correlated positively with UBA3 expression. Pathway activity correlated negatively with NEDP1 expression in PTEN-positive breast cancer patients, but not in PTEN-negative patients. We also demonstrate that high glucose conditions upregulate UBA3 mRNA by inhibiting UBA3 promoter methylation, and this upregulation results in the overactivation of PTEN neddylation in breast cancer cells. Conclusion: These data suggest a mechanism by which high glucose activates neddylation. PTEN is critical, if not indispensable, for MLN4924 suppression of tumor growth; PTEN status thus may help to identify MLN4924-responsive breast cancer patients.